INTELLECTUAL CAPITAL, COMPETITIVE ADVANTAGE, FINANCIAL PERFORMANCE AND COMPANY VALUE AMONG BANKING INDUSTRIES IN INDONESIA - Mulyasari, Windu; Murwaningsari, Etty (Advances in Social Sciences Research Journal, 2019)
Intangible asset in the form of intellectual capital becomes one of the factors that affect the performance and value of the company. Intellectual capital provides value added to the company, which encourages the production process and competitiveness. The progress of business processes has implications for the increase in company profits responded positively by the market. The intellectual capital issue is interesting to study, especially regarding its implications for company value. Intellectual capital influences the value of the company through competitive advantages that encourage the increase of company performance. The main objective of this study is to observe the effect of intellectual capital on company value. The author also hypothesized the mediating effect on the relationship, namely competitive advantage and financial performance. The study samples were taken from data on the Indonesia stock exchange, especially in the banking sector in Indonesia for the period of 2012-2015. The study results showed that there was an effect of intellectual capital on company value and that effect was mediated by competitive advantage and financial performance. Competitive advantage was also found to have an effect on company value and the relationship was mediated by company performance. Keywords: Intellectual Capital, Competitive Advantage, Company Performance, Company Value.